Assessment of quality of life in haemodialysis patients: A comparison of the Nottingham Health Profile and the Short Form 36 - Zengin, Neriman; Oren, Besey; Gul, Asiye; Ustundag, Hulya (Wiley, 2014)
This study aimed to compare the psychometric properties of the Nottingham Health Profile (NHP) and the Medical Outcomes Study Short Form Health Survey (SF-36), which evaluates health-related quality of life in haemodialysis patients. Data were gathered using the NHP and the SF-36. Quality of life scores obtained from the NHP and the SF-36 were compared according to sociodemographic characteristics. It was found that the internal consistency values of the NHP and the SF-36 were similar. The floor effect of the two NHP subscales and the ceiling effect of all the NHP subscales were higher than those pertaining to the. It was observed that the NHP mean subscale scores were higher than those of the SF-36, except for one subscale of the SF-36. There was a significant positive correlation between the similar subscales of the NHP and the SF-36 and between the total scores. These results seem to support the utility of the NHP and the SF-36 in evaluating quality of life in haemodialysis patients.
Keywords: Haemodialysis; Nhp; Nursing; Quality Of Life; Sf-36; Long-Term Survivors; Survey Questionnaires; Sf-36; Transplantation; People